2019
DOI: 10.5005/jp-journals-10024-2644
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Color Stability of Nanohybrid Direct and Indirect Resin-based Composites to Indian Spices: An In Vitro Study

Abstract: Aim: This study aimed to evaluate the color stability of nanohybrid direct resin-based composites and indirect resin-based composites to Indian spices. Materials and methods: Fifty samples of the nanohybrid resin-based composite (G-aenial) and the indirect resin-based composite (Adoro) were prepared using an acrylic template of dimension 8 mm × 3 mm. All the samples were polished with the Sof-Lex polishing kit. They were randomly divided into five groups and immersed in solutions of turmeric powder, tamarind e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Turmeric is known as “golden spice of India.” Curcumin, the yellow color pigment of turmeric,[ 11 ] is the major curcuminoid/polyphenolic compound which is of 9%. [ 12 ] They are hydrophobic in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Turmeric is known as “golden spice of India.” Curcumin, the yellow color pigment of turmeric,[ 11 ] is the major curcuminoid/polyphenolic compound which is of 9%. [ 12 ] They are hydrophobic in nature.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that composites with smaller filler sizes do not necessarily present low surface roughness and discoloration, implying that staining may depend upon monomer structure, as well as surface irregularities [ 14 21 ]. Monomer release may have an impact on color stability, and seemed to have led to reduced color stability in direct nanohybrid and nano-filled resin composites compared to indirect resin-based materials, irrespective of the staining agents and the F/P systems [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Any disagreement was resolved by discussion. After full text reading 178 studies 11,13–189 were included in the review (Figure 1).…”
Section: Methodsmentioning
confidence: 99%